2013
DOI: 10.1021/ja4000728
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Thermal Behavior of DNA Origami Nanostructures

Abstract: Understanding the thermodynamic properties of complex DNA nanostructures, including rationally designed two- and three-dimensional (2D and 3D, respectively) DNA origami, facilitates more accurate spatiotemporal control and effective functionalization of the structures by other elements. In this work fluorescein and tetramethylrhodamine (TAMRA), a Förster resonance energy transfer (FRET) dye pair, were incorporated into selected staples within various 2D and 3D DNA origami structures. We monitored the temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
110
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 34 publications
10
110
0
Order By: Relevance
“…Besides macrophages, note that most cell types discussed here may be considered phagocytic, including cancer cells and human umbilical vein endothelial cells (HUVECs) . Note that, as opposed to serum stability, we do not comprehensively address the notion of thermal stability here as the melting point of tile‐based and origami‐based DNA nanostructures can be readily designed to be higher than 37 °C, the temperature at which most cellular uptake studies take place, by adjusting the number and position of sticky ends in the structure.…”
Section: Governing Factors Of the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 99%
“…Besides macrophages, note that most cell types discussed here may be considered phagocytic, including cancer cells and human umbilical vein endothelial cells (HUVECs) . Note that, as opposed to serum stability, we do not comprehensively address the notion of thermal stability here as the melting point of tile‐based and origami‐based DNA nanostructures can be readily designed to be higher than 37 °C, the temperature at which most cellular uptake studies take place, by adjusting the number and position of sticky ends in the structure.…”
Section: Governing Factors Of the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 99%
“…One of the simplest possible perturbations is to reduce the concentration of staple strands [27]. In Fig.…”
Section: Perturbed Systemsmentioning
confidence: 99%
“…In particular, such an approach cannot describe cooperative interactions whereby the presence of a bound staple affects the binding of other staples to the scaffold. Recent evidence suggests that cooperative interactions affect origami folding significantly [23,26,27], leading to sharp formation transitions as the temperature is lowered and contributing to hysteresis in heating and cooling experiments.…”
Section: Introductionmentioning
confidence: 99%
“…First, most DNA constructs are composed of relatively short DNA duplexes that are prone to thermal denaturation. Although no studies have systematically examined thermal stability of DNA crystals, a number of studies of DNA tile and origami architectures have found that thermal denaturation in solution depends on a number of factors, including average duplex length, geometry, and crossover density . Further, because DNA is polyanionic, most DNA crystals require relatively high monovalent and/or divalent cations for crystallization and post‐crystallization stability .…”
Section: Introductionmentioning
confidence: 99%